Analisis Difusi Inovasi dan Pengembangan Budaya Kerja pada Hotel Maya Sanur Denpasar - Ni Ketut Arniti; I Komang Adi Putra (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid technological shift in the hospitality industry requires organizations to continuously adapt, particularly in integrating digital services and strengthening work culture. At Maya Sanur Resort & Spa, the diffusion of innovation has progressed unevenly, as a number of employees remain hesitant to adopt new digital systems and rely on manual work routines. This study aims to analyze how innovation is diffused within the organization and how work culture is developed to support these changes. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation involving managers and employees directly engaged in daily hotel operations. The data were analyzed through the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show four main points. First, innovation diffusion occurs through mass communication, interpersonal communication, and the organization’s social system. Second, the work culture emphasizes discipline, openness, cooperation, responsibility, and professionalism, which shape employees’ readiness to accept new practices. Third, the combination of innovation and cultural strengthening creates an adaptive and competitive work environment that enhances service quality and customer satisfaction. Fourth, management support through training, mentoring, and transparent communication plays a central role in accelerating innovation adoption. Overall, the study highlights that a strong work culture is essential to ensure the consistent and sustainable implementation of innovation in hospitality settings.